Self-assembled hierarchical pore MFI molecular sieve material and preparation method thereof

Through the dual-template agent method and mother liquor control technology, the problem of silicon-aluminum ratio and skeleton element control of multi-stage pore molecular sieve materials is solved, and the precise preparation of multi-stage pore structure is achieved, the stability and diffusion performance are improved, and the cost and experiments are reduced. mildness of the conditions.

CN119240730APending Publication Date: 2025-01-03YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411150994.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art cannot accurately control the silicon-aluminum ratio of multi-stage porous molecular sieve and the degree of removal of skeleton elements, resulting in insufficient structural collapse and diffusion performance.

Method used

The dual-template agent method is used to dissolve different types of template agents by combining strong polar and weak polar solvents to prepare multi-stage pore MFI molecular sieve materials, and the amount of non-silicon skeleton elements is controlled by mother liquor, and the structural composition and pore structure are optimized.

Benefits of technology

The precise control of the multi-stage pore structure is achieved, the stability and diffusion performance of the material are improved, the selectivity of water-acetone separation is better, and the mildness of cost and experimental conditions is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240730A_ABST
    Figure CN119240730A_ABST
Patent Text Reader

Abstract

The invention discloses a self-assembled hierarchical pore MFI molecular sieve material and a preparation method thereof, and belongs to the technical field of molecular sieve preparation. The preparation method comprises the following steps: blending the raw materials, aging, crystallizing, centrifuging, washing and roasting at high temperature to prepare the self-assembled hierarchical pore MFI molecular sieve material. The obtained self-assembled hierarchical pore MFI molecular sieve material has a three-stage pore structure of micropores, mesopores and macropores, and the macropores are communicated with one another. The materials used in the method are cheaper, the experimental conditions are milder, the crystallized product has a multi-stage through pore channel structure, and the method has good water-acetone separation selectivity and good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve preparation, and in particular relates to a self-assembled multi-level pore MFI molecular sieve material and a preparation method thereof. Background Art

[0002] Zeolite molecular sieve is a kind of inorganic microporous material with regular and uniform pore structure. It has excellent thermal stability, hydrothermal stability, adjustable acidity and unique shape selectivity. It is widely used in adsorption, catalysis and ion exchange. MFI zeolite molecular sieve has two sets of pore structures, namely, straight ten-membered ring pore parallel to the b axis, with a pore size of 0.54*0.56nm; and ten-membered ring zigzag pore parallel to the ac plane, with a pore size of 0.51*0.55nm. The special ten-membered ring pore structure provides MFI zeolite molecular sieve with excellent shape-selective catalytic selectivity.

[0003] Hierarchical molecular sieves combine the intrinsic characteristics of traditional molecular sieves with excellent diffusion performance brought by mesopores and macropore structures, effectively alleviating the diffusion limitation of micropore channels and the low accessibility, low detachability and low utilization of active sites, and have received widespread attention from researchers. At present, the commonly used method for preparing hierarchical molecular sieves in industry is acid or alkali post-treatment; acid or alkali post-treatment is to use acid or alkali to etch the molecular sieve to remove some of the skeleton elements to produce a mesoporous structure. The operation is convenient and the cost is low. This method has been applied in industry; however, this method cannot accurately control the degree of removal of skeleton elements, and excessive removal leads to structural collapse. At the same time, it is also impossible to control the silicon-aluminum ratio of the hierarchical molecular sieve. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] The dual template method used in the present invention is an in-situ synthesis method. Different types of templates are fully dissolved by combining strong polar and weak polar solvents, so that different types of templates can be fully dispersed and dissolved in a solution of silicon aluminum species, and a multi-level pore molecular sieve is prepared by crystallization after aging. The solvent molecules and template molecules remaining in the pores can be removed by drying and high-temperature calcination. The experimental method provided by the present invention is simple to operate and has low reagent cost. The molecular sieve structure has an excellent multi-level pore structure, which greatly improves its stability and diffusion performance. Moreover, since the multi-level pore structure is composed of smaller grains welded together, it has more hydroxyl density than conventional grains, and therefore has a more excellent water-acetone separation selectivity.

[0006] The present invention provides a multi-level porous MFI self-assembly preparation method that can accurately control the molar ratio of silicon and non-silicon skeleton elements of the material, has mild experimental conditions and low cost. The molar ratio of the skeleton elements is adjusted by controlling the amount of non-silicon skeleton elements of the material through the mother liquid, and the dual template agent and strong and weak polar solvents are used at the same time to optimize the structural composition and pore organization.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a self-assembled multi-level porous MFI molecular sieve material.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0010] The aluminum source is dissolved in a strong polar solvent to obtain solution A; the first template and the alkali source are dissolved in a strong polar solvent to obtain solution B; the second template is dissolved in a weak polar solvent to obtain solution C;

[0011] Under stirring, solutions A, B, and C are simultaneously added dropwise to the framework element dispersion. After the addition is completed, the mixture is stirred in a sealed manner until the mixture is uniform, thereby obtaining a molecular sieve mother solution;

[0012] The molecular sieve mother liquid is crystallized at a constant temperature, washed and dried, and then calcined or oxidatively etched to obtain a self-assembled multi-level pore MFI molecular sieve material.

[0013] As a preferred embodiment of the method for preparing the self-assembled multi-level porous MFI molecular sieve material of the present invention, the aluminum source includes one or more of aluminum isopropoxide, aluminum nitrate, aluminum sulfate, sodium metaaluminate, aluminum oxide, and aluminum hydroxide; the alkali source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia water, barium hydroxide, and calcium hydroxide.

[0014] As a preferred embodiment of the method for preparing the self-assembled multi-level porous MFI molecular sieve material of the present invention, the first template comprises an organic quaternary ammonium salt, the number of carbon atoms in a single organic carbon chain in the organic quaternary ammonium salt does not exceed 16, and the organic quaternary ammonium salt comprises one or more of tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, trimethylethylammonium salt, trimethylpropylammonium salt, trimethylbutylammonium salt, trimethylpentylammonium salt, dimethyldiethylammonium salt, dimethyldipropylammonium salt, dimethyldibutylammonium salt, diethyldipropylammonium salt, and methylethyldipropylammonium salt; the second template comprises an organic amine, and the organic amine comprises one or more of a saturated secondary amine, an unsaturated secondary amine, a secondary amine alcohol, or an unsaturated amine alcohol.

[0015] As a preferred scheme for the preparation method of the self-assembled multi-level porous MFI molecular sieve material of the present invention, the strong polar solvent includes one or more of deionized water, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the weak polar solvent includes one or more of ethanol, ethylene glycol, propanol, propylene glycol, glycerol, acetone, ether, chloroform, and pyridine; and the volume proportion of the strong polar solvent in the molecular sieve mother liquor is ≥30%.

[0016] As a preferred scheme for the preparation method of the self-assembled multi-level porous MFI molecular sieve material of the present invention, the crystallization comprises the following steps: the crystallization temperature is 120-175°C and the crystallization time is 1-2 days; the calcination is carried out in pure oxygen or oxygen-enriched air, the heating rate is 3-8°C / min, the calcination temperature is 450-800°C and the calcination time is 2-6h; the oxidation etching adopts 20%-30% hydrogen peroxide.

[0017] As a preferred scheme for the preparation method of the self-assembled multi-level porous MFI molecular sieve material of the present invention, the skeleton elements of the molecular sieve material include one or more multivalent metal elements such as silicon, aluminum, boron, germanium, titanium, magnesium, iron, gallium, zirconium, and cobalt.

[0018] As a preferred solution of the method for preparing the self-assembled multi-level porous MFI molecular sieve material of the present invention, the source of the silicon element includes one or more of silica sol, white carbon black, gas-phase SiO2, and sodium silicate.

[0019] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a self-assembled multi-level pore MFI molecular sieve material. The MFI molecular sieve material has a three-level pore structure, including micropores, mesopores and macropores, and the pores are interconnected; wherein the mesopore diameter is 2nm to 50nm, and the macropore diameter is 50nm to 2μm.

[0020] As a preferred embodiment of the self-assembled multi-level porous MFI molecular sieve material of the present invention, the molar ratio of silicon to multivalent metal elements in the molecular sieve material is ≥100:1.

[0021] As a preferred embodiment of the self-assembled multi-level porous MFI molecular sieve material of the present invention, the molecular sieve material has a high hydroxyl density and has a better water-acetone separation selectivity.

[0022] Beneficial effects of the present invention:

[0023] (1) The method provided by the present invention has mild experimental conditions and low cost. The MFI molecular sieve material prepared by the present invention has an excellent multi-level pore structure, which greatly improves its stability and diffusion performance.

[0024] (2) The self-assembled multi-level pore MFI molecular sieve material provided by the present invention is a polycrystalline structure, and has abundant through-going mesopores inside and between the grains. The stacking faults between the grains produce large pores that penetrate the polycrystalline structure, greatly improving its stability and diffusion performance. Due to the stacking fault growth between the grains, the grains are welded together by "bonding", which not only has a stable structure, but also has a higher hydroxyl density than conventional grains, and therefore has a better water-acetone separation selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0026] Figure 1 This is the SEM image of the self-assembled multi-level pore MFI molecular sieve material in Example 1.

[0027] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve in Example 1 are shown.

[0028] Figure 3 This is the SEM image of the self-assembled multi-level pore MFI molecular sieve material in Example 2.

[0029] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve in Example 2 are shown.

[0030] Figure 5 This is the SEM image of the self-assembled multi-level pore MFI molecular sieve material in Example 3.

[0031] Figure 6 The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve in Example 3 are shown.

[0032] Figure 7 This is the SEM image of the MFI molecular sieve material in Comparative Example 1.

[0033] Figure 8 The nitrogen adsorption-desorption curve and pore size distribution curve of the MFI molecular sieve material in Comparative Example 1 are shown.

[0034] Fig. 9 This is the SEM image of the MFI molecular sieve material in Comparative Example 2.

[0035] Fig.10These are the nitrogen adsorption-desorption curve and pore size distribution curve of the MFI molecular sieve material in Comparative Example 2.

[0036] Fig.11 The XRD diagrams of the MFI molecular sieves prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are shown. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0041] The performance of the material prepared in the embodiment of the present invention was tested as follows:

[0042] Silanol density M Si-OH The absorbance peak A and total specific surface area S corresponding to the silanol group per gram of molecular sieve measured by in situ infrared total The absorbance peak A corresponding to the hydroxyl group is the terminal silanol peak (3740 cm -1 ), hydrogen-bonded terminal silanol peak (3720 cm -1 ), ortho-silanol peak (3690~3680cm -1 ) and silanol nest (~3500cm -1 ) is the sum of the absorbances of the four hydroxyl peaks.

[0043] Separation selectivity of water-acetone solution: At 298K, 25wt% acetone-water system is used as the separation liquid, and the same mass of MFI molecular sieve material is placed in the separator. The separator is divided into a feed chamber and a vaporization chamber, and the vaporization chamber is connected to the vacuum system. The pervaporated acetone and water are collected in a liquid nitrogen cold trap, and the acetone content of the feed liquid and the collection is analyzed by gas chromatography. The separation coefficient of water is α 水 / 丙酮 =(y 水 / y丙酮 ) / (x 水 / x 丙酮 ), where x and y represent the mass fractions in the permeate collection and the feed solution, respectively.

[0044] Example 1

[0045] This embodiment provides a method for preparing a self-assembled multi-level porous MFI molecular sieve material, specifically:

[0046] 1. Weigh 1.021 g of aluminum isopropoxide as an aluminum source, dissolve it in 20.0 g of deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;

[0047] 2. Weigh 3.17 g NaOH as the alkaline source and 8.06 g tetrapropylammonium bromide as the first template, dissolve the two in 50.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;

[0048] 3. Weigh 38.77 g of dibutylamine as the second template and dissolve it in 75.00 mL of anhydrous ethanol. Stir at room temperature for 0.5 h in a sealed container. This is referred to as solution C.

[0049] 4. Weigh 100.0g silica sol (SiO2 content 30wt%) solution as silicon source, and slowly drop solutions A, B, and C into the silica sol solution while stirring, and continue stirring at room temperature for 1.5h. During the stirring process, pay attention to the state of the mixed solution. Once a gel-like solid appears, increase the stirring speed to make the gel-like solid disperse rapidly under the stirring and shearing action; after the addition of solutions A, B, and C is completed, stir at room temperature for 2h to complete the preparation of the molecular sieve mother solution;

[0050] 5. The molecular sieve mother liquor was transferred to a PTFE-lined reactor, and crystallized at a constant temperature of 140°C for 48 hours at a rotation speed of 20 rpm. After the crystallization, the molecular sieve mother liquid crystallized to form an MFI molecular sieve. The crystallized product was centrifuged and washed several times, dried at 100°C overnight, and then calcined at 550°C in an oxygen atmosphere for 6 hours to remove the organic amine template used in the synthesis process, thereby obtaining a self-assembled multi-level porous MFI molecular sieve material with a silicon-aluminum molar ratio of 100:1.

[0051] Figure 1 This is an SEM image of the self-assembled multi-level pore MFI molecular sieve material prepared in Example 1 of the present invention. It can be seen from the figure that the MFI molecular sieve material prepared in the embodiment of the present invention is composed of stacked grains with a size of <2μm, and there are macropores with a size of more than 100nm between the grains; the microscopic polycrystalline size of the self-assembled multi-level pore MFI molecular sieve material prepared in this embodiment is 6 to 8 microns.

[0052] Figure 2The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve prepared in this embodiment show that after P / P0>0.4, there is an obvious mesoporous hysteresis loop, which means that the MFI material prepared in this embodiment has a mesoporous structure. At the same time, according to the pore size distribution curve, it can be seen that the MFI material prepared in this embodiment has intrinsic micropores of 0.51 nm in size, and has a mesoporous structure of 5.1 and 6.8 nm in size.

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that the mass of aluminum isopropoxide is adjusted to 0.255 g, that is, the silicon-aluminum ratio is 400, and the rest of the preparation process is the same as that of embodiment 1 to obtain a self-assembled multi-level pore MFI molecular sieve material.

[0055] Figure 3 This is the SEM image of the self-assembled multi-level pore MFI molecular sieve material prepared in this embodiment. It can be seen that the self-assembled multi-level pore MFI molecular sieve material prepared in this embodiment has a polycrystalline morphology, the polycrystalline size is 6 to 8 microns, the polycrystalline grains are formed by the accumulation of single crystal grains with a size of <4μm, and there are macropores of more than 100nm between the single crystal grains.

[0056] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve prepared in this embodiment show that after P / P0>0.4, there is an obvious mesoporous hysteresis loop, which means that the MFI material prepared in this embodiment has a mesoporous structure. At the same time, according to the pore size distribution curve, it can be seen that the MFI material prepared in this embodiment has intrinsic micropores of 0.51 nm in size, and has a mesoporous structure of 6.8 and 8.1 nm in size.

[0057] Example 3

[0058] The difference between this embodiment and embodiment 1 is that the second template solvent is adjusted to ethylene glycol, and the rest of the preparation process is the same as that of embodiment 1 to prepare a self-assembled multi-level pore MFI molecular sieve material.

[0059] Figure 5 This is an SEM image of the self-assembled multi-level pore MFI molecular sieve material prepared in this embodiment. It can be seen from the figure that the self-assembled multi-level pore MFI molecular sieve material prepared in this embodiment has a polycrystalline morphology, the polycrystalline size is 6 to 8 microns, the polycrystalline grains are formed by the accumulation of single crystal grains with a size of <4μm, and there are macropores of more than 100nm between the single crystal grains.

[0060] Figure 6The nitrogen adsorption-desorption curve and pore size distribution curve of the self-assembled multi-level pore MFI molecular sieve in this embodiment show that after P / P0>0.4, there is an obvious mesoporous hysteresis loop, which means that the MFI material prepared in this embodiment has a mesoporous structure. At the same time, according to the pore size distribution curve, it can be seen that the MFI material prepared in this embodiment has intrinsic micropores of 0.51 nm in size, and has a mesoporous structure of 6.8 and 8.1 nm in size.

[0061] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.

[0062] Table 1

[0063] Example 1 Example 2 Example 3 <![CDATA[S total ( / m 2 ·g -1 )]]> 346.83 342.29 343.65 <![CDATA[V total ( / mL·g -1 )]]> 0.3501 0.3464 0.3521 <![CDATA[V micro ( / cm 3 ·g -1 )]]> 0.2015 0.2132 0.2048 Micropore diameter d / nm 0.51 0.51 0.51 Minimum mesopore diameter d / nm 6.8、8.1 5.1、6.8 6.8、8.1 <![CDATA[M Si-OH / (A·m -2 )]]> 0.213 0.215 0.215 <![CDATA[Water-acetone adsorption selectivity α 水 / 丙酮 > 137.7 135.2 136.8

[0064] As can be seen from the above table, adjusting the feed silicon-aluminum ratio has no significant effect on the specific surface area, pore volume and water-acetone adsorption selectivity of the self-assembled multi-level pore MFI molecular sieve material, but the size of the most mesopores increases significantly. This is because the silicon-aluminum ratio increases, the skeleton aluminum decreases, the introduced skeleton defects decrease, and the size of the generated mesopores also decreases accordingly; since the diameter of acetone molecules is within 1nm, the mesopores above 5nm have a weak effect on the diffusion of acetone molecules, so the water-acetone adsorption selectivity in Examples 1 to 3 has no significant effect. According to the results in the above table, the best technical effect can be obtained when the silicon-aluminum ratio in the present invention is 100.

[0065] Example 4

[0066] The difference between this embodiment and embodiment 1 is that the aluminum isopropoxide is adjusted to Al(NO3)3·9H2O, and the rest of the preparation process is the same as that of embodiment 1 to obtain a self-assembled multi-level pore MFI molecular sieve material.

[0067] Example 5

[0068] The difference between this embodiment and embodiment 1 is that aluminum isopropoxide is replaced by aluminum sulfate, and the rest of the preparation process is the same as that of embodiment 1 to prepare a self-assembled multi-level pore MFI molecular sieve material.

[0069] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.

[0070] Table 2

[0071]

[0072]

[0073] It can be seen from the above table that adjusting the type of aluminum source has no significant effect on the specific surface area, pore volume and water-acetone adsorption selectivity of the self-assembled multi-level pore MFI molecular sieve material. This is because the three aluminum sources have good solubility in water, but aluminum isopropoxide will produce isopropanol after dissolving in water, and isopropanol can be used as a weak polar solvent; according to the results in the above table, the best technical effect can be obtained when the aluminum source in the present invention is aluminum isopropoxide.

[0074] Example 6

[0075] The difference between this embodiment and embodiment 1 is that the crystallization time is adjusted to 36 hours, and the rest of the preparation process is the same as that of embodiment 1, and a self-assembled multi-level pore MFI molecular sieve material is prepared.

[0076] Example 7

[0077] The difference between this embodiment and embodiment 1 is that the crystallization time is adjusted to 24 hours, and the rest of the preparation process is the same as that of embodiment 1, and a self-assembled multi-level pore MFI molecular sieve material is prepared.

[0078] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.

[0079] Table 3

[0080] Example 1 Example 6 Example 7 <![CDATA[S total ( / m 2 ·g -1 )]]> 348.18 338.82 335.97 <![CDATA[V total ( / mL·g -1 )]]> 0.3451 0.3351 0.3342 <![CDATA[V micro ( / cm 3 ·g -1 )]]> 0.2055 0.2005 0.1971 Micropore diameter d / nm 0.51 0.51 0.51 Minimum mesopore diameter d / nm 6.8、8.1 6.8、8.1 6.8、8.1 <![CDATA[M Si-OH / (A·m -2 )]]> 0.215 0.205 0.201 <![CDATA[Water-acetone adsorption selectivity α 水 / 丙酮 > 139.1 130.1 130.2

[0081] It can be seen from the above table that adjusting the crystallization time has a slightly significant effect on the water-acetone adsorption selectivity of the self-assembled multi-level pore MFI molecular sieve material. This is because the increase in crystallization time is conducive to the formation of crystallized products and the improvement of crystallinity. According to the results in the above table, the best technical effect can be obtained when the crystallization time is 48h in the present invention.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that the silica sol is adjusted to gas-phase SiO2, the amount of gas-phase SiO2 used is consistent with the amount of SiO2 in the silica sol, and deionized water with the same water content as that in the silica sol is added at the same time to make the gas-phase SiO2 uniformly dispersed in the deionized water. The rest of the preparation process is the same as that in embodiment 1 to obtain a self-assembled multi-level pore MFI molecular sieve material.

[0084] Example 9

[0085] The difference between this embodiment and embodiment 1 is that the silica sol is adjusted to an aqueous solution of sodium silicate, the silicon content in the aqueous sodium silicate solution is consistent with that in the silica sol, and the rest of the preparation process is the same as that in embodiment 1 to obtain a self-assembled multi-level pore MFI molecular sieve material.

[0086] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.

[0087] Table 4

[0088] Example 1 Example 8 Example 9 <![CDATA[S total ( / m 2 ·g -1 )]]> 348.18 341.44 336.37 <![CDATA[V total ( / mL·g -1 )]]> 0.3451 0.3435 0.3384 <![CDATA[V micro ( / cm 3 ·g -1 )]]> 0.2055 0.2005 0.2001 Micropore diameter d / nm 0.51 0.51 0.51 Minimum mesopore diameter d / nm 6.8、8.1 6.8、8.1 6.8、8.1 <![CDATA[M Si-OH / (A·m -2 )]]> 0.215 0.205 0.201 <![CDATA[Water-acetone adsorption selectivity α 水 / 丙酮 > 139.1 133.9 134.2

[0089] It can be seen from the above table that adjusting the silicon source has a significant effect on the performance of the self-assembled multi-level pore MFI molecular sieve material. This is because the silicon dioxide particles in the silica sol are nanometer-sized and have higher dispersibility than gas-phase SiO2 and sodium silicate. According to the results in the above table, the best technical effect can be obtained when the silicon source in the present invention is silica sol.

[0090] Comparative Example 1

[0091] The difference between this comparative example and Example 1 is that the solvent of the adjustment solution C is deionized water, and no alcohol solvent is introduced in the preparation process to prepare the self-assembled multi-level pore MFI molecular sieve material.

[0092] Figure 7 This is the SEM image of the self-assembled multi-level porous MFI molecular sieve material prepared in this comparative example. It can be seen from the figure that the crystallization result is a "cross" morphology of grains with a rough surface, and there is a "step" morphology caused by obvious secondary growth at the intersection of the "cross". The grain size distribution is large, and the maximum grain size is close to 7μm.

[0093] Figure 8 The nitrogen adsorption-desorption curve and pore size distribution curve of the MFI molecular sieve material in Comparative Example 1 show that after P / P0>0.45, there is an obvious mesoporous hysteresis loop, which means that the MFI material prepared in this embodiment has a mesoporous structure. At the same time, according to the pore size distribution curve, it can be seen that the MFI material prepared in this embodiment has intrinsic micropores of 0.51 nm in size, as well as an ultra-microporous structure of 1.5 nm and a mesoporous group of 8.1 nm in size.

[0094] Comparative Example 2

[0095] The difference between this comparative example and Example 1 is that no alcohol solvent and no second template agent are introduced during the preparation process to prepare the self-assembled multi-level pore MFI molecular sieve material.

[0096] Fig. 9 This is a SEM image of the self-assembled multi-level porous MFI molecular sieve material prepared in this comparative example. It can be seen from the figure that the crystallization result is a "cross" shaped grain with a smooth surface, and the grain size distribution is relatively uniform, and the grain size is between 2 and 3 μm.

[0097] Fig.10The nitrogen adsorption-desorption curve and pore size distribution curve of the MFI molecular sieve material in Comparative Example 2 show that after P / P0>0.45, there is an obvious mesoporous hysteresis loop, which means that the MFI material prepared in this embodiment has a mesoporous structure. At the same time, according to the pore size distribution curve, it can be seen that the MFI material prepared in this embodiment has intrinsic micropores of 0.51 nm in size, as well as an ultra-microporous structure of 1.5 nm and a mesoporous structure of 8.1 nm in size.

[0098] Fig.11 The XRD diagrams of the MFI molecular sieves prepared in Examples 1 to 3 and Comparative Examples 1 to 2 show that the peak positions of the materials prepared in different Examples and Comparative Examples correspond one to one with the standard MFI structure, that is, the materials prepared in different Examples and Comparative Examples all have MFI structures.

[0099] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.

[0100] Table 5

[0101]

[0102]

[0103] It can be seen from the above table that compared with hydrothermal synthesis (Comparative Example 1, Comparative Example 2), the total specific surface area of ​​the self-assembled multi-level pore MFI molecular sieve material prepared in the dual template alcohol-water solvent system is reduced, but the overall pore volume and micropore volume are increased. This is mainly because the introduction of mesopores and macropores reduces the proportion of micropores in the material.

[0104] The self-assembled multi-level porous MFI molecular sieve material prepared in the dual-template alcohol-water solvent system has higher adsorption selectivity in the water-acetone system. This is mainly because the self-assembled multi-level porous MFI molecular sieve material prepared in the dual-template alcohol-water solvent system has more silicon hydroxyl groups, which are easier to form hydrogen bonds with water molecules and adsorb water molecules; compared with water molecules, the polarity of acetone molecules is relatively small, and due to the steric hindrance of the methyl group in the molecular structure, it is difficult for the carbonyl group to form hydrogen bonds with the silicon hydroxyl group, thereby reducing the adsorption of acetone.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the crystallization temperature is adjusted to 100° C., and the rest of the preparation process is the same as that of Example 1, and the obtained product is an amorphous material.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that the crystallization temperature is adjusted to 180° C., and the rest of the preparation processes are the same as those in Example 1, and the obtained product is a quartz material.

[0109] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.

[0110] Table 6

[0111] Example 1 Comparative Example 3 Comparative Example 4 <![CDATA[S total ( / m 2 ·g -1 )]]> 348.18 172.43 6.52 <![CDATA[V total ( / mL·g -1 )]]> 0.3451 0.1393 0.0066 <![CDATA[V micro ( / cm 3 ·g -1 )]]> 0.2055 0.0723 0.0000 Micropore diameter d / nm 0.51 1.4 — Minimum mesopore diameter d / nm 6.8、8.1 9.3 — <![CDATA[M Si-OH / (A·m -2 )]]> 0.215 0.032 0.010 <![CDATA[Water-acetone adsorption selectivity α 水 / 丙酮 > 139.1 4.1 1.0

[0112] As can be seen from the above table, by lowering or increasing the crystallization temperature (Comparative Example 3, Comparative Example 4), it is impossible to prepare a self-assembled multi-level porous MFI molecular sieve material under the same dual-template alcohol-water solvent system; the low crystallization temperature is not enough to produce crystal nuclei in the mother liquor to obtain amorphous silicon aluminum oxide; increasing the crystallization temperature results in a denser quartz material. The surface of amorphous silicon aluminum oxide contains some hydroxyl groups, so it has a certain water-acetone adsorption selectivity. Quartz is a densely crystalline silicon oxide material without a pore structure. Even if there are some silicon hydroxyl groups on the surface, it is difficult to separate water and acetone; therefore, it does not have water-acetone adsorption selectivity.

[0113] The present invention prepares a self-assembled multi-level pore MFI molecular sieve material by blending, aging, crystallizing, centrifuging, washing and high-temperature calcining the raw materials. The obtained self-assembled multi-level pore MFI molecular sieve material has a three-level pore structure of micropores, mesopores and macropores, and the macropores are interconnected. The materials used in the present invention are cheaper and the experimental conditions are milder. The crystallized product has a multi-level through-channel structure and has good water-acetone separation selectivity, and has good industrial application prospects.

[0114] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a self-assembled multi-level porous MFI molecular sieve material, characterized in that: include, The aluminum source is dissolved in a strong polar solvent to obtain solution A; the first template and the alkali source are dissolved in a strong polar solvent to obtain solution B; the second template is dissolved in a weak polar solvent to obtain solution C; Under stirring, solutions A, B, and C are simultaneously added dropwise to the framework element dispersion. After the addition is completed, the mixture is stirred in a sealed manner until the mixture is uniform, thereby obtaining a molecular sieve mother solution; The molecular sieve mother liquid is crystallized at a constant temperature, washed and dried, and then calcined or oxidatively etched to obtain a self-assembled multi-level pore MFI molecular sieve material.

2. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 1, characterized in that: The aluminum source includes one or more of aluminum isopropoxide, aluminum nitrate, aluminum sulfate, sodium aluminate, aluminum oxide, and aluminum hydroxide; the alkali source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia water, barium hydroxide, and calcium hydroxide.

3. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 1, characterized in that: The first template includes an organic quaternary ammonium salt, in which the number of carbon atoms in a single organic carbon chain does not exceed 16, and the organic quaternary ammonium salt includes one or more of tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, trimethylethylammonium salt, trimethylpropylammonium salt, trimethylbutylammonium salt, trimethylpentylammonium salt, dimethyldiethylammonium salt, dimethyldipropylammonium salt, dimethyldibutylammonium salt, diethyldipropylammonium salt, and methylethyldipropylammonium salt; the second template includes an organic amine, and the organic amine includes one or more of a saturated secondary amine, an unsaturated secondary amine, a secondary amine alcohol, or an unsaturated amine alcohol.

4. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 1, characterized in that: The strong polar solvent includes one or more of deionized water, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the weak polar solvent includes one or more of ethanol, ethylene glycol, propanol, propylene glycol, glycerol, acetone, ether, chloroform, and pyridine; the volume proportion of the strong polar solvent in the molecular sieve mother liquor is ≥30%.

5. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 1, characterized in that: The crystallization, wherein the crystallization temperature is 120-175° C., and the crystallization time is 1-2 days; the calcination is calcined in pure oxygen or oxygen-enriched air, wherein the heating rate is 3-8° C. / min, the calcination temperature is 450-800° C., and the calcination time is 2-6 hours; the oxidation etching uses 20%-30% hydrogen peroxide.

6. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 1, characterized in that: The skeleton elements of the molecular sieve material include one or more polyvalent metal elements such as silicon, aluminum, boron, germanium, titanium, magnesium, iron, gallium, zirconium, and cobalt.

7. The method for preparing the self-assembled multi-level porous MFI molecular sieve material according to claim 6, characterized in that: The source of the silicon element includes one or more of silica sol, white carbon black, gas phase SiO2, and sodium silicate.

8. A self-assembled multi-level porous MFI molecular sieve material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The MFI molecular sieve material has a three-level pore structure, including micropores, mesopores and macropores, and the pores are interconnected; wherein the pore diameter of the mesopores is 2nm to 50nm, and the pore diameter of the macropores is 50nm to 2μm.

9. The self-assembled multi-level pore MFI molecular sieve material according to claim 8, characterized in that: The molar ratio of silicon to multivalent metal elements in the molecular sieve material is ≥100:

1.

10. The self-assembled multi-level pore MFI molecular sieve material according to claim 8, characterized in that: The molecular sieve material has a high hydroxyl density and has a more excellent water-acetone separation selectivity.